Geologic causatives of the stratigraphic and structural heterogeneties of Baharyia formation, based on their seismic interpretation, Razzak field, Western Desert, Egypt - Mostafa M. Metwally; Ahmed S. A. Abu El-Ata (Geomechanics and Geophysics for Geo-Energy and Geo-Resources, 2024)
Abstract Evaluation of seismic attributes and seismic reflection characteristics analysis of Razzak Field was undertaken by subdividing the study area rock units. There are four seismo-facies units of varying parameters from top to bottom. These units are comparable to the Apollonia and Khoman Formations; the Abu-Roash Formation; Baharyia Formation and Alamein Formation. The seismo-facies unit 1 of the Apollonia and Khoman Formations reveal parallel to sub-parallel layering, with thickness increases northwards. The lithological distribution consists of limestone with minor clay intercalations with facies varying from middle neritic graded to outer neritic. Unit 2 of the Abu-Roash Formation shows divergent layering, with a thickness increasing gradually northwards and eastwards. The lithological distribution shows predominance of carbonate, sandstone occurring in minor portions and laterally graded into shale with littoral facies ranging to inner and middle neritic facies. Unit 3 of the Baharyia Formation reveals chaotic and oblique layering with a time thickness increases towards northeast and southwest parts, the lithological distribution exhibited sand and shale with minor limestone streaks, with facies varied changed from continental to inner-middle neritic, unit 4 of the Alamein Formation shows variation from parallel-subparallel orientation to oblique and chaotic with thickness increasing towards northwards and eastwards, the lithological distribution exhibited dolomitic limestone with minor streaks of limestone with facies varied from middle neritic facies to outer neritic and bathyal. Finally, the results are integrated to build up a seismo-stratigraphic model of the evaluated area of the northwestern Desert of Egypt. Seismic interpretation involves the construction of structure contour maps, in terms of time and depth, on the tops of the Apollonia, Abu-Roash, Baharyia and Alamein Formations. These maps show three structural closures, due to folding, that are dissected by NW–SE faults, analysis of relevant structural and stratigraphic seismic attributes such as root-mean-square amplitude, local structural dip, variance, ISO frequency component, sweetness and acoustic impedance average energy applied on reservoir tops, to enhance the visibility of faults, geological interpretation and the physical parameters of the subsurface related to lithology and stratigraphy for reservoir characterization. Finally, the results obtained are used to construct a seismic structural model. Integration of seismic and stratigraphic data is used to build a geological model of the northwestern Desert of Egypt.